Case law: A review of selected pharmaceutical patents litigated in the UK courts during 2022 - Crawford, Sarah-Jane; O'Brien, Harry Melville; Stones, James Alexander (British Journal of Pharmacy, 2023)
Patents lie at the interface between technology and law. This review provides a summary of four high profile cases from 2022 in which patents in the pharmaceutical or medical space were litigated in the UK Courts. The first case concerns Astellas' patent for Betmiga (mirabegron) for overactive bladder. The second case involves a patent to Bristol-Meyers Squibb for Eliquis (apixaban) for thromboembolic disorders. The third case concerns Novartis' patent for Exjade (deferasirox) for use in the treatment of conditions involving excess iron in the blood caused by haemochromatosis, etc. In the final case, Novartis defended its patent for Gilenya (fingolimod) as a disease modifying therapy for relapsing remitting multiple sclerosis. The article aims to focus on the technology behind the patents and to provide an insight into how science interacts with law in the context of patent enforcement and infringement.